PENGARUH PUPUK FOSFAT DAN INOKULASI CENDAWAN MIKORIZA ARBUSKULAR TERHADAP PERTUMBUHAN DAN HASIL KEDELAI HITAM (Glycine soja) VARIETAS MUTIARA-2 - Yadi, Rama Julkarnaen (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2020)
The purpose of this research was to know the interaction effect from phosphate fertilizers and mycorrhizal arbuscular fungi inoculation to the growth and yield of black soybean (Glycine soja) Varieties of Mutiara-2 and to know relationship between growth and yield component of black soybean (Glycine soja) Varieties of Mutiara-2. This research was conducted at Wanasaba Kidul, Talun Sub-District, Cirebon Regency, West Java, Indonesia from June until September 2018. This research is located at altitude of 20 meters above sea levels (masl) and rainfall type method is rainfall type C (rather wet). This research was arranged by Completely Randomized Block Design Factorial, with two factors and repeated three times. First factor is phosphate fertilizers rate with three levels (50, 100, 150 kg ha-1) per plots. Second factor is mycorrhizal arbuscular fungi inoculation rate with three levels (200, 400, 600 kg ha-1). The result showed that phosphate fertilizers gave significantly effect to flowering age, weight of dry pods per plant and weight of dry seeds per plant. Mycorrhizal arbuscular fungi inoculation gave significantly effect number of trifoliate leaves at 28 Days After Planted (DAP). There were interaction between phosphate fertilizers and mycorrhizal arbuscular fungi inoculation to plant height 21 DPA and 28 DPA, root volume and weight of dry seeds per plot.